Bacterial nasopharyngeal carriage following infant immunization with pneumococcal conjugate vaccines according to a 2+1 schedule in children in South Africa: an exploratory analysis of two clinical trials. (1st December 2020) - Nunes, Marta C.; Moreira, Marta; Koen, Anthonet; van Niekerk, Nadia; Jose, Lisa; Cutland, Clare L.; François, Nancy; Schoonbroodt, Sonia; Ruiz-Guiñazú, Javier; Yarzabal, Juan Pablo; Borys, Dorota; Schuerman, Lode; et al.
ABSTRACT: Background : We evaluated bacterial nasopharyngeal carriage (NPC) prevalence and cumulative acquisition following 7-valent pneumococcal conjugate vaccine (PCV7) or pneumococcal non-typeable Haemophilus influenzae protein D conjugate vaccine (PHiD-CV) administration. Methods : Participants were children from two clinical trials in a South African center who received PCV7 (n = 250) or PHiD-CV (n = 100) at 6 weeks, 14 weeks, and 9–10 months of age, and were enrolled between Dec2009-Apr2010 and Mar2009-May2010 in the PCV7 and PHiD-CV studies, respectively. Sample collection, most microbiological assessments, and data re-analysis methods were identical. Results : NPC prevalence of any pneumococcal serotype was 18.5% and 17.0% at pre-vaccination, and 63.1% and 67.3% in 24–27 month-old children among PCV7 and PHiD-CV recipients, respectively. In 24–27 month-old children, 96.1% and 99.0% of PCV7 and PHiD-CV recipients had acquired ≥1 pneumococcal serotype, 53.7% and 62.9% ≥1 PCV7 serotype, 1.5%, and 3.1% ≥1 of serotypes 1, 5 or 7F, 23.2% and 19.6% serotype 6A, 23.2% and 21.7% serotype 19A, 88.7%, and 91.0% H. influenzae, and 50.3% and 62.9% Staphylococcus aureus, respectively. Conclusions : This analysis of two concurrent clinical trials did not reveal differences in bacterial NPC prevalence or acquisition in PCV7- and PHiD-CV-vaccinated children. Trial registration : South African National Clinical Trial Register (NHREC DOH-27-0511-299); ClinicalTrials.gov (NCT00829010).